Rapid recovery of tigers Panthera tigris in Parsa Wildlife Reserve, Nepal. Issue 1 (7th August 2017) - Lamichhane, Babu Ram; Pokheral, Chiranjibi Prasad; Poudel, Shashank; Adhikari, Dipendra; Giri, Sailendra Raj; Bhattarai, Santosh; Bhatta, Tek Raj; Pickles, Rob; Amin, Rajan; Acharya, Krishna Prasad; Dhakal, Maheshwar; Regmi, Uba Raj; et al.
Abstract: Information on density and abundance of globally threatened species such as tigers Panthera tigris is essential for effective conservation as well as to evaluate the success of conservation programmes. We monitored tigers in Parsa Widlife Reserve, Nepal, using camera traps, in 2013, 2014 and 2016. Once believed to be a sink for tigers from adjacent Chitwan National Park, Parsa now provides a new hope for tigers. Spatially explicit capture–recapture analysis over 3 survey years revealed an increase in tiger density from 0.78 to 1.38 individuals per 100 km 2 from 2013 to 2016. The tiger abundance was estimated to be seven (6–13), 11 (10–16) and 17 (17–20) in 2013, 2014 and 2016, respectively. Resettlement of communities from the core area, reduced anthropogenic pressure, and improved security have made Parsa Wildlife Reserve a suitable habitat for tigers. Tiger abundance increased considerably within a 5 km radius of the evacuated village sites, from two in 2013 to eight in 2014 and 10 in 2016. Population turnover has remained moderate (< 30% per year), with persistence of individuals in multiple years. Dispersing tigers from Chitwan's source population accounted for a large portion (c. 40%) of the tigers detected in Parsa. Conservation efforts along with annual monitoring should be continued in Parsa to sustain the increase and monitor the persistence of tigers. The Chitwan–Parsa complex should be managed as a single ecological unit for conserving the Endangered tiger and other wide-ranging species.